Serial mom [videorecording (Blu-Ray)] - Waters, John, 1946-; Waters, John, 1946-; Turner, Kathleen, 1954-; Waterston, Sam; Lake, Ricki (Scream Factory, 2017)
Beverly Sutphin, seemingly the perfect suburban homemaker, is driven to murder by the everyday annoyances in her neighborhood.